Early Buddhist Transmission and Trade Networks: Mobility and Exchange within and beyond the Northwestern Borderlands of South Asia by Jason Neelis. - Osto, Douglas (Buddhist Studies Review, 2013)
Early Buddhist Transmission and Trade Networks: Mobility and Exchange within and beyond the Northwestern Borderlands of South Asia by Jason Neelis. Brill, 2011. xx+372pp., hb. €126.00/US$179.00. ISBN 13: 9789004181595.